Financial inclusion, financial stability and economic growth in developing countries - Ali, Hamisu Sadi (2016)
The number of individuals and firms that have access and uses formal financial services provided by the mainstream financial sectors determines the performance of the financial sector of the economy; higher level of financial inclusion could automatically increase banking liquidity and hence provides more loanable funds for viable investments, the multiplier effect of this may positively influence the level of employment and reduce income inequality as well poverty. The present study has the overall objective of investigating the impacts of financial inclusion in sustaining financial stability and economic growth in developing countries.The first specific objective intends to examine the effect of migrant workers‟ remittance on financial inclusion in developing countries based on dynamic panel GMM estimation technique. In this objective 46 developing countries were selected and the time period of the study is 2004-2010. The empirical finding reveals that migrant workers remittances have positive and significant impact on financial inclusion in the sample countries.The result reveals that 1% increase in migrant workers remittance could increase financial inclusion by 0.067% in the sample countries. Migrant workers remittance therefore becomes an important financial inflow that stimulates financial sector development in the countries investigated.The second specific objective based on 52 developing countries for the time period of 2004-2010 also applied dynamic panel GMM estimation technique, the objective is to examine the effect of financial inclusion on financial stability in developing countries.The main empirical finding shows that financial inclusion positively influences financial stability, the result suggest that 1% increase in financial inclusion positively stimulates financial stability by 0.375%. This therefore emphasizes the relevance of higher access and usage of formal financial services in controlling the shocks of financial instability, hence financial inclusion stimulates the stability of the financial system.The third specific objective also applied dynamic panel GMM estimation technique across 48 developing countries for the period of 2004-2010; the objective is to investigate the impact of financial inclusion on economic growth in developing countries. The key impirical finding reveals that financial inclusion have positive and significant impact on economic growth in developing countries. The result highlight that 1% increase in financial inclusion could stimulates economic growth to increase by 0.132%, this finding confirmed the essential functions that access and usage of formal financial services plays in promoting the overall economic performance in developing countries. Therefore it is imperative from the policy perspectives to encourage uses as well as provide enabling policies and suitable environments for smooth accessibility of formal financial services considering its diverse positive effects on financial sector development as well as overall economic growth.